Response of greater prairie-chickens to natural and anthropogenic disturbance on Fort Riley - Gehrt, Jacquelyn (Kansas State University, 2021)
Greater Prairie-chickens (Tympanuchus cupido) historically occupied 20 states within the contiguous United States and four Canadian provinces; however, due to habitat degradation and loss, they are currently found in 11 states; only four of which have a stable population. Kansas supports a relatively large abundance of Greater Prairie-chickens, where the Flint Hills ecoregion historically supported the largest population of all ecoregions. In the past decade, however, the Flint Hills population has declined to an estimated 8,334 individuals in 2021 from 34,180 individuals in 2015 due to changes and intensification of grassland management practices. The Fort Riley Military Reservation in the northwest portion of the Flint Hills ecoregion is one of a few areas within the ecoregion that does not implement grazing or vast annual burning. The Greater Prairie-chicken population within Fort Riley has remained stable over the past 25 years despite being constrained by surrounding landscape features and development. To understand why this population is doing relatively well compared to populations in surrounding areas, I trapped, collared, and tracked 46 female Greater Prairie-chickens from March-April 2019-2020 on Fort Riley. My goals with this project were to assess female survival, nest survival, resource selection, and space use during the breeding season (Apr-Aug) on the military reservation. Despite being free from grazing and annual burning, Fort Riley experiences fairly constant military activity, which may elicit responses from Greater Prairie-chickens. I used known-fate and nest survival models in Program MARK to estimate female survival and nest success of Greater Prairie-chickens. I estimated breeding season survival as 0.2750 ± 0.0650 (SE) and nest survival as 0.2643 ± 0.0689 (SE), which are average and high for the Flint Hills, respectively. I used logistic regression models to assess resource selection by Greater Prairie-chicken females. I analyzed landscape features, vegetation variables, and burn mosaics to understand which features had the most influence on resource selection and found landscape features to impact resource selection. Females avoided trees within Fort Riley (probability of use greatest at 2,000 m from nearest tree) at a greater margin than any other study in Kansas. Lastly I calculated home ranges, net, and total daily displacement across the lekking, nesting, and post-nesting stages of the breeding season to understand how Greater Prairie-chickens responded to military activity. Home ranges were slightly smaller than those in surrounding areas yet breeding stage trends remained constant (lekking: 238 ± 43 ha, nesting: 115 ± 20 ha, post-nesting: 113 ± 11 ha) when compared to past literature. Lastly, total daily movements did not differ significantly between days where activity was occurring versus when it was not (training occurring: 1,121 ± 127m, training not occurring: 1,309 ± 63m). My findings suggest that despite being in a constrained environment, Greater Prairie-chickens on Fort Riley are doing well demographically and are not showing signs of being affected by military activity. Because of the constrained environment, however, it is important for land managers to monitor woody encroachment and other tall vertical features as this may lead to loss of habitat and cause potential negative effects on the Fort Riley population.
Keywords: Greater prairie-chicken; Resource selection; Space use; Survival; Grasslands